Surgical Treatment of Male Infertility - Selahittin Çayan (Düzce Tıp Fakültesi Dergisi, 2022)
Male infertility may occur due to obstructive and non-obstructive reasons, and some pathologies may be corrected with surgical and medical treatment. Such treatment may increase the possibility of spontaneous pregnancy, the success of assisted reproductive technology, and also testicular sperm retrieval rate. This review will focus on surgical treatment alternatives in infertile males. Although treatment options for varicocele in infertile men include open surgical, radiologic, and laparoscopic approaches; microsurgical varicocele repair has the highest improvement in postoperative sperm parameters with lower complication rates. Recent advances in microsurgical anastomosis techniques have increased the patency rate for proximal epididymal obstruction. Although treatment options for distal ejaculatory duct obstruction include endoscopic resection, balloon dilatation, and laser incision/excision, transurethral resection of the ejaculatory duct (TURED), is still the primary gold standard treatment of distal ejaculatory duct obstruction. The testicular sperm retrieval rate has increased with the management of correctable pathologies in men with non-obstructive azoospermia. In case of treatment failure of correctable or uncorrectable pathologies of male factor infertility, surgical sperm obtained from the urogenital tract may necessary for assisted reproductive technology. Surgical success rates for male infertility and the success of surgical sperm obtained procedures have increased dramatically over the last decades attributable to the development of microsurgical techniques and endoscopic equipment, instrumentation, and techniques.